Immunogenicity and safety of COVID-19 vaccine in lung cancer patients receiving anticancer treatment: A prospective multicenter cohort study. Issue 6 (30th November 2022) - Nakashima, Kei; Ishida, Masayuki; Matsui, Hiroki; Yoshida, Chihiro; Nagai, Tatsuya; Shiraga, Minoru; Nakaoka, Hiroshi; Otsuka, Yoshihito; Nakagama, Yu; Kaku, Natsuko; Nitahara, Yuko; Kido, Yasutoshi; et al.
ABSTRACT: This study assessed the immunogenicity and safety of the BNT162b2 mRNA vaccine in lung cancer patients receiving anticancer treatment. We enrolled lung cancer patients receiving anticancer treatment and non-cancer patients; all participants were fully vaccinated with the BNT162b2 vaccine. Blood samples were collected before the first and second vaccinations and 4 ± 1 weeks after the second vaccination. Anti-severe respiratory syndrome coronavirus-2 (SARS-CoV-2) spike protein S1 subunit receptor-binding domain antibody titers were measured using the Architect SARS-CoV-2 IgG II Quant and Elecsys Anti-SARS-CoV-2 S assays. Fifty-five lung cancer patients and 38 non-cancer patients were included in the immunogenicity analysis. Lung cancer patients showed significant increase in the geometric mean antibody concentration, which was significantly lower than that in the non-cancer patients after the first (30 vs. 121 AU/mL, p  < .001 on Architect; 4.0 vs 1.2 U/mL, p  < .001 on Elecsys) and second vaccinations (1632 vs. 3472 AU/mL, p  = .005 on Architect; 213 vs 573 A/mL, p  = .002 on Elecsys). The adjusted odds ratio (aOR) for seroprotection was significantly lower ( p  < .05) in lung cancer patients than that in non-cancer patients. Analysis of the anticancer treatment types showed that the aOR for seroprotection was significantly lower ( p  < .05) in lung cancer patients receiving cytotoxic agents. They showed no increase in adverse reactions. BNT162b2 vaccination in lung cancer patients undergoing anticancer treatment significantly increased ( p  < .05) antibody titers and showed acceptable safety. Immunogenicity in these patients could be inadequate compared with that in non-cancer patients.